1999
DOI: 10.21273/hortsci.34.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Sweetpotato Clone Tolerance to Weed Interference

Abstract: Field experiments were conducted to assess how sweetpotato [Ipomoea batatas (L.) Lam.] clones interfere with weeds and how clones tolerate weed interference. Eleven clones with architecturally different canopies were evaluated for yield, canopy surface area and dry mass, weed dry mass, and light interception at ground level. A 2-fold difference in ground area covered by canopy surface area was observed among the eleven clones 42 days after planting, and a 3-fold difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…There is growing international interest in integrated approaches to weed control in sweetpotato, incorporating herbicides, clonal tolerance (La Bonte et al 1999), allelopathic effects (Harrison and Peterson 1991;Reinhardt et al 1993;Peterson and Harrison 1995) and the critical period of crop-weed competition (Nedunzhiyan et al 1998). An assessment of the early weed population in this trial allowed the final yield loss due to plant competition to be predicted.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing international interest in integrated approaches to weed control in sweetpotato, incorporating herbicides, clonal tolerance (La Bonte et al 1999), allelopathic effects (Harrison and Peterson 1991;Reinhardt et al 1993;Peterson and Harrison 1995) and the critical period of crop-weed competition (Nedunzhiyan et al 1998). An assessment of the early weed population in this trial allowed the final yield loss due to plant competition to be predicted.…”
Section: Resultsmentioning
confidence: 99%
“…However, hand weeding had much more impact on sweetpotato yields than did the type of tillage system used. The severe impact of weeds was not unexpected, because previous studies have shown that sweetpotato yield losses due to weed interference are acute when weeds are not controlled (LaBonte et al 1999, Seem et al 2003. The killed-cover crop production system may reduce but not prevent weed losses.…”
Section: Discussionmentioning
confidence: 98%
“…1999. Development of the leaf canopy varies among sweetpotato cultivars; thus, they are differentially affected by weed interference (LaBonte et al 1999). Beauregard has a thinner canopy than many other commercial sweetpotato varieties (Harrison and LaBonte 2003, Yencho and Pecota 2007, and it is not very tolerant to weed competition (LaBonte et al 1999).…”
Section: Methodsmentioning
confidence: 99%
“…Plant and leaf morphology affects canopy coverage, which can affect weed interference, soil erosion, soil moisture loss, and photosynthetic activity (Cavalcante et al, 2018;Harrison and Jackson, 2011;Labonte et al, 1999). Commercial sweetpotatoes are most susceptible to weed competition early in the season when weed interference can dramatically affect yields (Cavalcante et al, 2018;Meyers et al, 2010;Seem et al, 2003;Semidey et al, 1987).…”
Section: Discussionmentioning
confidence: 99%